2005
DOI: 10.1007/s00417-005-0112-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection of paravascular retinal cysts before using OCT in a highly myopic patient

Abstract: Paravascular retinal rarefaction as well as pseudohole formation caused by vitreoretinal adhesion on retinal vessels was detected in this patient using OCT. OCT might be useful to detect early-stage retinal pathologies caused by paravascular vitreoretinal traction in highly myopic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 9 publications
0
15
1
Order By: Relevance
“…These results coincide with other authors. 2,9 However, it is important to note that we have not identified any association between a longer AL and MF, even though, we observed that eyes with MF were longer than those without MF. This fact makes us consider the AL as an insufficient factor to develop MF on its own.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…These results coincide with other authors. 2,9 However, it is important to note that we have not identified any association between a longer AL and MF, even though, we observed that eyes with MF were longer than those without MF. This fact makes us consider the AL as an insufficient factor to develop MF on its own.…”
Section: Discussioncontrasting
confidence: 61%
“…They distinguish intra-and outer-ocular wall factors in the development of MF. 2,5,9 The outer ocular forces include chorioretinal atrophy, posterior staphyloma, and longer AL. The intraocular forces include epiretinal membrane, vitreomacular traction, residula focal vitreoretinal adhesion, and retinal vessel stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association with high myopia is consistent with other studies in which PVCs have been shown to be related to high myopia or elongation of the eye. 5 Vascular microfolds and paravascular retinal holes may develop secondary to PVCs. PVCs were not related to decreased visual acuity in the BDES and have little clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…OCT images centred on the fovea showed that all eyes had a retinal thickening with tractional retinal oedema (figure 1). OCT images along the retinal arcade vessels showed paravascular lamellar holes with retinal cysts in five eyes 5. These abnormalities were observed along the same retinal vessels.…”
mentioning
confidence: 77%